The effects of high inflation on public finances in the euro area: Based on the analysis by the Eurosystem members of the Working Group on Public Finance - Krzysztof Bańkowski; Cristina Checherita-Westphal; Julia Jesionek; Philip Muggenthaler (European Central Bank (ECB), 2023)
The recent spike in inflation, unprecedented in the history of the Economic and Monetary Union (EMU), has had major consequences for all areas of the economy, including public finances. This paper aims to provide a detailed assessment of the effects of high inflation on fiscal accounts in the euro area. Relying on the wealth of expertise in the Eurosystem - within the Working Group on Public Finance - it documents spending indexation arrangements in all euro area countries. Thanks to this knowledge, the ECB's fiscal projection platform, which is the primary evaluation tool for this study, establishes a realistic link between prices and fiscal variables. The results of this paper bring into question the conventional wisdom on the overall positive effects of inflation on fiscal accounts. Indeed, the simulations point to adverse effects from the recent inflation surge, mainly triggered by an external supply shock, on budget balances during 2022-24. This is even without taking into account the negative impact of inflation on the real economy, mainly through monetary policy tightening. The analysis also points to the important role of the denominator effect for debt-to-GDP ratios, which may fall even in the absence of benefits for the budget balance. Finally, the analysis reveals a high degree of heterogeneity across countries
Keywords: C3; E3; E6; 330; macroeconomic simulations; euro area; inflation; fiscal policy